Constructive and collegial peer-review as a necessary precursor to data-driven environmental policy. (January 2020) - Gerwing, Travis G.; Rash, Joshua A.
Abstract: As academic output increases, editors and reviewers are inundated with manuscripts, a phenomenon that has resulted in extended wait times, and, in many cases, suboptimal reviews. This is particularly an issue if data-driven environmental policy is the goal, as peer-review is an important step in this process. Numerous systemic fixes have been suggested to improve peer-review; however, we question the value of system-wide change if peer-reviewers continue to engage in behaviour that is not collegial, or in-keeping with the sentiment behind rigorous peer-review. We provide nine best practice statements that compliment proposed system-wide changes with the goal to improve the process of peer-review by helping to develop reviewer codes of conduct. These statements focus only upon reviewer conduct, not issues such as conflicts of interest or confidentiality. It is our hope that data driven improvements to peer-review models, and reviewer codes of conduct will make the peer-review process more efficient and collegial. Such improvements are necessary to promote novel and innovative academic research, as well as to enhance the diversity of voices present in the academic literature.